Contributions to the knowledge of Neotropical Castianeirinae (Araneae: Corinnidae): redescription of Castianeira spinipalpis Mello-Leitão, 1945, with first description of the male, and description of a new Myrmecotypus O. Pickard-Cambridge, 1894 from the Bolivian Moxos plains - Pett, Brogan L.; Perger, Robert (Zootaxa, 2021)
Two Neotropical species of the subfamily Castianeirinae are treated herein. Castianeira spinipalpis Mello-Leitão, 1945 was described from a single female specimen; we provide a redescription of the female and the male is described for the first time. The species is newly recorded from Paraguay and Bolivia. Also, Myrmecotypus rubioi sp. nov. is described from the Bolivian Moxos plains, a tropical savanna ecoregion of the Beni department of northern Bolivia. The new species can be distinguished from others in the genus by having tibia I spination 3-2, coxa II whitish (the remainder dark), and a unique male palpal embolus with two broad embolic discs basal to the embolus tip.